2015
DOI: 10.1007/s10741-015-9503-x
|View full text |Cite
|
Sign up to set email alerts
|

The short-term and long-term effects of tolvaptan in patients with heart failure: a meta-analysis of randomized controlled trials

Abstract: A comprehensive evaluation of the benefits of tolvaptan for the management of heart failure (HF) is lacking. The objective of this meta-analysis was to assess the short-term and long-term effects of tolvaptan in patients with HF. Articles were searched from PubMed, MEDLINE and Cochrane Library before March 31, 2015. Randomized controlled trials enrolling adult HF patients and reporting the all-cause mortality, cardiac events, body weight change or changes of serum electrolytes including sodium, potassium and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…A previous meta-analysis showed that TLV elevated the serum creatinine level slightly [11]; however, there was no significant difference in morbidity associated with renal dysfunction between TLV and control groups in EVEREST study [26]. The changes in creatinine levels that occur during successful decongestion therapy do not necessarily indicate the same adverse prognosis [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous meta-analysis showed that TLV elevated the serum creatinine level slightly [11]; however, there was no significant difference in morbidity associated with renal dysfunction between TLV and control groups in EVEREST study [26]. The changes in creatinine levels that occur during successful decongestion therapy do not necessarily indicate the same adverse prognosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that TLV is a safe and effective drug for the treatment of euvolemic and hypervolemic hyponatremia as well as for patients with HF [9, 10]. Three meta-analyses were performed to investigate the efficacy and safety of TLV treatment in patients hospitalised for HF [1113]; however, these analyses were primarily focused on chronic heart failure (CHF). Since the publication of these meta-analyses, many new clinical trials have been performed to investigate the efficacy and safety of TVL in patients with AHF [8, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings of significant changes (decrease in body weight, increase in urine volume, and increase in serum sodium level) with add-on tolvaptan therapy support the results of previous meta-analyses. [10][11][12][13] Alkaf, et al 12) analyzed seven double-blind RCTs and found that tolvaptan had no effect on all-cause mortality, but its body weight, urine volume, and serum sodium level improved significantly. Xiong, et al 10) integrated 10 RCTs and found that there was no long-term benefit of tolvaptan, but body weight, urine volume, and serum sodium level improved significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2015, meta-analyses of tolvaptan have been reported. [10][11][12][13][14] In recent years, several randomized controlled trials (RCTs) performed in actual clinical settings in Japan have also been reported, calling attention to the need for integrated analysis of differences between the doses of tolvaptan used in previous clinical studies in Europe and North America and the doses currently used in Japan. We performed a meta-analysis of RCTs in Europe, North America, and Japan.…”
mentioning
confidence: 99%
“…Moreover, the package insert also recommends not administering TLV over a prolonged period if fluid retention disappears and/or body weight is within the target range. However, a study has revealed that some patients require TLV over a prolonged period (4). In addition, the long-term use of TLV is reported to reduce the dosage of loop diuretics (5).…”
Section: Introductionmentioning
confidence: 99%